Когнітивні методи навчання у процесі вивчення фармацевтичного менеджменту і маркетингу - Ткаченко, Наталя Олександрівна; Демченко, Вікторія Олександрівна; Книш, Євгеній Григорович; Ткаченко, Н. А.; Демченко, В. А.; Кныш, Е. Г.; Tkachenko, N. O.; Demchenko, V. O.; Knysh, Ye. G. (ЗДМУ, 2014)
Розглянули окремі когнітивні методи (емпатії, символічного бачення, порівнянь, фактів, досліджень, помилок, прогнозування) і визначили проблеми та особливості їх використання у процесі вивчення фармацевтичного менеджменту та маркетингу. Рассмотрены отдельные когнитивные методы (эмпатии, символического видения, сравнений, фактов, исследований, ошибок, прогнозирования) и определены проблемы и особенности их использования в процессе изучения фармацевтического менеджмента и маркетинга. Some cognitive methods (method of empathy, the method of the symbolic vision, method comparisons, the method of the facts, research method, the method of error prediction method) have been considered in the article, and the problems and peculiarities of their use in the study of pharmaceutical management and marketing have been identiﬁ ed. Key words: cognitive training methods, pharmaceutical management and marketing.
Когнитивные методы обучения в процессе изучения фармацевтического менеджмента и маркетинга
Cognitive teaching methods in the process of studying pharmaceutical management and marketing
Keywords: когнітивні методи навчання; фармацевтичний менеджмент і маркетинг; когнитивные методы обучения; фармацевтический менеджмент и маркетинг; cognitive training methods; pharmaceutical management and marketing.